Real-time Synchrophasor Data Compression Technique with Phasor Interpolation and Extrapolation - Fang Zhang; Meiqian Liu; Zixuan Zhang; Jinghan He; Wenzhong Gao (Journal of Modern Power Systems and Clean Energy, 2023)
To completely eliminate the time delays caused by phasor data compressions for real-time synchrophasor applications, a real-time synchrophasor data compression (RSDC) is proposed in this paper. The two-way rotation characteristic and elliptical trajectory of dynamic synchrophasors are introduced first to enhance the compressions along with a fast solving method for elliptical trajectory fitting equations. The RSDC for phasor data compression and reconstruction is then proposed by combining the interpolation and extrapolation compressions. The proposed RSDC is verified by both the actual phasor measurement data recorded in a two-phase short-circuit incident and a subsynchronous oscillation incident, and the synthetic dynamic synchrophasors. It is also compared with two previous real-time phasor data compression techniques, i.e., phasor swing door trending (PSDT) and exception and swing door trending (SDT) data compression (ESDC). The verification results demonstrate that RSDC can achieve significantly higher compression ratios for offline applications with the interpolation and the zero-delay phasor data compression with the extrapolation for real-time applications simultaneously.